Three Cheers! Otaki - Mackay, Christina (Architectural History Aotearoa, 2007)
The District Plan Heritage Register for Ōtaki, Kāpiti Coast includes nine buildings from 1890s; two residences, a children's home, a maternity hospital, solicitors' offices, a church and three hotels – the Jubilee (1891), Telegraph (1895) and Railway (1891) (Kapiti Coast District Council "Heritage Register" v 1, s I, pp 9-11). The Telegraph and Railway hotels continue to serve patrons today, but the Jubilee Hotel is currently a community house, the House of Hope. Two other hotels operated in Ōtaki in 1890s, the Family (1881) and the Central (1893). This paper focuses on the development and role of these hotels within Ōtaki in 1890s and then tracks the changing patterns of use against the alterations to the building fabric since that time.